The use of colchicine as an elicitor increases the accumulation of phenolics and flavonoids in Java cardamom (Amomum compactum) leaves - WARAS NURCHOLIS; SYARIFAH IIS AISYAH; NURUL KOMALA; HEDER DJAMALUDIN; FACHRUR RIZAL MAHENDRA; RAIHAN PERMANA PUTRA (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Nurcholis W, Aisyah SI, Komala N, Djamaludin H, Mahendra FR, Putra RP. 2026. The use of colchicine as an elicitor increases the accumulation of phenolics and flavonoids in Java cardamom (Amomum compactum) leaves. Biodiversitas 27 (3): d270326. https://doi.org/10.13057/biodiv/d270326. Java cardamom (Amomum compactum) is a medicinal plant valued for its secondary metabolites. This study examined the effects of colchicine treatment on plant morphology, physiology, and phytochemical content using vegetative buds collected from a wild population in West Java, Indonesia. A total of 80 buds were treated with colchicine at 0% (control), 0.1%, 0.2%, and 0.3% concentrations. Morphological parameters—including plant height, leaf number, and tiller count—were measured at 18 weeks after planting. Total Phenolic Content (TPC), Total Flavonoid Content (TFC), and antioxidant capacity were evaluated using ABTS, DPPH, FRAP, and CUPRAC assays. Colchicine treatment caused dose-dependent reductions in plant height and tiller number, with mild leaf shape alterations, but did not induce significant changes in chlorophyll content or stomatal density. TPC and TFC were significantly increased across all treated groups, with the highest TPC at 0.1% colchicine and the highest TFC and ABTS antioxidant activity at 0.3%. Flow cytometry confirmed that colchicine did not induce polyploidy in A. compactum. Bioinformatic analysis based on Arabidopsis thaliana orthologs revealed upregulation of genes involved in cytokinin signaling (RR17, RAP2.4, GIS2) and phenolic biosynthesis (LAP5, KMD3), supporting a possible hormonal mechanism underlying phytochemical enhancement. The results suggest that colchicine acts as a chemical elicitor, enhancing secondary metabolism without chromosomal duplication. These findings support the potential of colchicine for improving medicinal quality in Java cardamom. Further studies are recommended to optimize treatment parameters and validate gene-level responses directly in A. compactum for targeted phytochemical enhancement.